A Comparative Study on Levels of Aggression in boys and Girls with Hearing Impairment - Shaista Majid, Nadia Nawaz, Muhammad Bilal (JIE, 2024)
The research was designed to compare the level of aggression in hearingimpaired boys and girls. The descriptive method of research was opted to conduct the study. The population comprised of hearing-impaired students of ages 13-19 years studying in classes 6-10 at Special Education Institution for Hearing Impaired Children in Rawalpindi. The sample size was 198 hearing impaired students (98 male and 100 female) drawn by simple random sampling technique. Aggression Questionnaire developed by Buss and Perry (1992) was used as a research tool. Pilot testing of the tool was conducted on 20 hearing impaired students (10 male and 10 female) of ages 13-19 years. The results of pilot testing showed high reliability of the tool i.e. 0.90 for this study. The finding of this study revealed that verbal aggression among all students was very high as compared to all other types/subscales of Aggression Questionnaire; physical aggression, anger and hostility. The levels of physical aggression and hostility were found comparatively at the same level while the levels of anger were at the least in comparison to different subscales. It was concluded that hearing-impaired boys have high levels of aggression as compared to hearing-impaired girls thus early identification of aggression was recommended.